Concentración de pesticidas organoclorados en aire del sur de la cuenca del Plata: un año de muestreo - Bilos, Claudio (2012)
Polyurethane foam passive air samplers (n=20) were deployed across the Southern del Plata basin to assess concentrations and distributions of Organochlorine Pesticides (OCPs) for ≈ 3-4 months periods all over a year. Annual average concentration of OCPs ranged from 326 to 9000 pg/m3 with predominance of endosulfans (Endo). Annual averages of Endo (230-8936 pg/m3) are higher than reported values for other countries from this region (Brazil, Bolivia, Chile y Colombia: 114-898 pg/m3). Maximum values correspond to the warm period in areas of intense soybean culture: North of BsAs and South of E. Ríos and Santa Fe (3072-21521 pg/m3). Concentrations of DDTs (12-235 pg/m3) are an order of magnitude lower than the sites where it is used against malaria at present (India: 5356pg/m3; South of Mexico: 2360 pg/m3) but DDT/DDE ratio (1.1-6.8) >1 suggests a relatively fresh contribution, possibly due to the use of dicofol that presents this compound impurity. The HCHs showed high concentrations in Zárate (801-8348 pg/m3) where they predominanted (66% of the total) with an α/γHCHs ratio ≈7, similar to the technical mixture suggesting a fresh contribution. In the metropolitan area chlordanes prevailed (83-691 pg/m3) representing 5-45% of the total, especially in Buenos Aires City, where the cis/trans-chlordane relationship >> 1.6 indicates a fresh contribution It was concluded that the OCPs have different spatial distribution: higher concentrations in agriculrure areas; diversity in composition of pesticides and higher values of clordanes in urban areas. Concentrations and relationship values suggest non-legal inputs or long range transport.